1990
DOI: 10.1097/00132586-199008000-00049
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Blockade with Vecuronium in Paediatric Patients with Burn Injury

Abstract: 1 The effect of body surface area (BSA) burn injury on neuromuscular pharmacodynamics of vecuronium was evaluated. 2 The neuromuscular responses of 15 burned children were compared with those in five controls. 3 The effective dose for 50% suppression of twitch tension (ED50) was 34 ,ug kg-' for patients with < 40% BSA burn, 55 ,ug kg-1 for 40-60% BSA burn, and 65 ,ug kg-1 for patients with > 60% BSA burn. These values were significantly higher than the value for control patients, which was 18 pug kg-'.4 Burn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Mills and Martyn demonstrated that ED 50 and ED 95 of vecuronium were significantly (97.5±20.3 s) (P< 0.01). Our results are also in keeping with the results of another study with vecuronium increased in burned children (2). But this study did not examine the recovery from neuromuscular (10).…”
Section: Introduction Materials and Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…Mills and Martyn demonstrated that ED 50 and ED 95 of vecuronium were significantly (97.5±20.3 s) (P< 0.01). Our results are also in keeping with the results of another study with vecuronium increased in burned children (2). But this study did not examine the recovery from neuromuscular (10).…”
Section: Introduction Materials and Methodssupporting
confidence: 90%
“…Thermal injury is known to produce resistance to The study was approved by the Hospital's Ethics nondepolarizing muscle relaxants (1)(2)(3)(4)(5)(6)(7). The neuro-Committee and written informed consent was muscular responses to vecuronium in children with obtained from parents.…”
Section: Introduction Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically, there is an increased requirement for d-TC a n d o t h e r nondepolarizing muscle relaxants. 6,18,20,22,23,25,26 T h ere are some discrepancies, however, concerning the onset of resistance in rats and humans. Dwerstag et a1.,6 reported that resistance to atracurium in humans with a 33% burn was maximal at 15-40 days and attenuated by 100 days.…”
Section: Discussionmentioning
confidence: 99%